Mobilization Intervention for Post-operative Appendectomy Recovery Process in Appendicitis Patients - Iif Taufiq El Haque; Ade Fitriani; Elis Roslianti; Shofia Siti Adawiah (Jurnal Vocational Nursing Sciences (VNUS), 2023)
Objective: This case study aims to describe the effect of early mobilization on the post-appendectomy recovery process in appendicitis patients. Method: The research design used was a case study with a nursing care approach covering assessments, formulating diagnoses, interventions, implementation, and evaluation, which were carried out for 4 days from Mar 30 to Apr 3, 2023, in the Orchid Room of the Banjar City BLUD. The enforcement of nursing diagnoses refers to the IDHS, SIKI, and SLKI, and nursing evaluations are documented using the SOAPIER method. This case study uses a descriptive method with one respondent involved, with data collection techniques including observation, interviews, documentation, and physical examination.Result: Nursing diagnosis of decreased physical mobility (D.0054) associated with postoperative physical weakness. 4 days of mobilization interventions were carried out with a duration of 30 minutes per day. After intervention, nursing problems related to patient mobility disabilities were resolved by increasing muscle strength, which was initially muscle strength in the upper extremities, namely 4 and 3 in the lower extremities, to 5 in the muscle strength of the upper extremities and 4 in the lower extremities, as well as an increase in the patient's independent activity patterns.Conclusion: The provision of mobilization interventions is useful in improving the recovery process after appendectomy, and the benefits of therapy will be maximized if it is carried out regularly and gradually.